Cathodic electrophoretic deposition (EPD) of phenylenediamine-modified graphene oxide (GO) for anti-corrosion protection of metal surfaces. (February 2019) - Hwang, Min-Ju; Kim, Myeong-Gi; Kim, Sanghoon; Kim, Ye Chan; Seo, Hee Won; Cho, Jung Keun; Park, In-Kyung; Suhr, Jonghwan; Moon, Hyungpil; Koo, Ja Choon; Choi, Hyouk Ryeol; Kim, Kwang Jin; et al.
Abstract: Anti-corrosion metal protection of the 2D structured graphene oxide (GO) was investigated in this study using its intrinsic impermeability against reactive molecules stemming from the small geometric pore size and π-orbital repelling fields of graphene. The electrophoretic deposition (EPD) of GO sheets on metals is an attractive coating method but the negatively-charged GO only allows the anodic EPD process, which makes it difficult to achieve high-quality coating layers due to gas bubbling and electrochemical oxidation of metals. Thus, we imposed the positive charge to GO sheets using p -phenylenediamine (PPD) and successfully carried out the cathodic EPD in the ethanol aqueous solution. The cathodic EPD of GO on cupper provided a linear growth rate with both deposition time and voltage providing the thickness over 6.0 μm in a void-free and robust feature, which could hardly be achieved by other coating methods. Converting the GO coating to the reduced GO (RGO) by thermal reduction, we successfully increased the RGO adhesion strength up to the highest adhesion grade of 5B in the cross-cut adhesion test. An excellent anti-corrosion protection capability of the developed RGO coating was demonstrated by a decreased corrosion current density and increased corrosion potential in potentiodynamic polarization analysis. Graphical abstract: Image 1